Inconsistency between linearized Thomas–Fermi approximation and electron-ionized impurity scattering rate in the first Born approximation. (31st October 2018) - Marchetti, Gionni
Abstract: We show that by computing the electron-impurity scattering rate at the first order via Fermi's golden rule, and assuming that the localized impurity potential is of Yukawa form, one obtains a wave vector transfer distribution which is inconsistent with the finite temperature linearized Thomas–Fermi approximation for n -type semiconductors. Our previous findings show that this is not the case for the carrier nondegenerate dynamics, because the average wave vector transferred being in general negligible in this regime. Moreover, we examine the behavior of the electron-impurity differential cross-sections in the first Born approximation for relevant values of the wave vector transfer. We find that in the majority of collisions, the scattering probabilities differ at the most by 1% from the estimates computed by means of the impurity potential at random phase approximation level.